Strengthening Local Cultural Identity Abroad: Pitepangan and Tembang Dolanan as Educational Media at the Indonesian Community Centre Muar, Malaysia - Anis Ismawati; Lasmi; Sinta Fitri Novia; Sulaf Muhammad Arifuro’is; Umi Cholwatun; Revina Yuliani; Octo Dendy Andriyanto (Jurnal Soeropati, 2025)
The Javanese Language and Literature Education Study Program at Universitas Negeri Surabaya contributes to the Kampus Merdeka humanitarian project, which aims to preserve and promote Javanese culture to the younger migrant workers by utilizing engaging and relevant educational media. This activity aims to strengthen their identity as descendants of Indonesians, particularly through the Javanese language. In the pitepangan (greetings) lesson, students were encouraged to learn how to introduce themselves in Javanese. In the tembang dolanan (traditional children's songs) session, they were taught to sing three traditional songs: Menthok-Menthok, Lesung Jumenglung, and Gundhul-Gundhul Pacul. The learning activities used the Empowerment-Based Collaboration (EBC) method, emphasizing active collaboration among all involved parties. The steps of the method included initial observation, demonstration, discussion, practice, and documentation. The activity results showed a 75% increase in students' ability to introduce themselves in Javanese, and 82% of the students were able to sing tembang dolanan in Javanese. Overall, the understanding of local culture increased by 78%, accompanied by high enthusiasm throughout the learning process. Through the use of pitepangan and tembang dolanan as educational media, the learning model became more varied, enabling students to absorb the material more effectively.